Are Recycling People Also Saving? Costliness Matters - Wei, Sheng; Xu, Jiaqi; She, Shengxiang; Wang, Yan; Zhang, Ying (Frontiers in Psychology, 2021)
In view of the fact that vigorously promoting recycling has become a viable means to promote sustainable development, it is important to better understand the impact of recycling efforts on subsequent resource saving behavior. This research empirically examines the effects of recycling efforts on subsequent resource saving by analyzing the survey data of 356 college students in China. The recycling efforts, environmental self-identity and feeling of pride were measured using existing scales while saving behaviors and recycling cost were measured by developing new scales. Partial least squares structural equation modelling was performed to test the structural relationships among recycling efforts, environmental self-identity, feeling of pride and saving behaviors. Further, the moderation role of recycling cost was tested. The results showed that (1) saving behaviors could be classified into two types based on their costliness; (2) recycling efforts have a positive effect on costless saving behaviors, while having a negative effect on costly saving behaviors; (3) both the positive and negative effect of recycling efforts on resource saving is mediated by pride feeling and environmental self-identity; and (4) recycling cost negatively moderates the effects of recycling efforts on pride feeling. We discuss the theoretical and managerial implications of the findings.